A conservation assessment of the terrestrial ecoregions of Latin America and the Caribbean (World Bank, 1995)
"Important report on the status of conservation efforts in Latin America. This biogeographical approach delimited five major ecosystems, 11 major habitat types, and 191 ecoregions. Appendices provide extensive database on the ecoregions, and nine well-constructed maps of Latin America illustrate the bioregions, major habitats, ecoregions, mangrove, conservation status, biological distinctiveness, and conservation priorities. The foldout map of 'Ecoregions of Latin America and the Caribbean' is a major contribution"--Handbook of Latin American Studies, v. 57